Scutellaria barbata D.Don (SBD) extracts suppressed tumor growth, metastasis and angiogenesis in Prostate cancer via PI3K/Akt pathway - Dongya Sheng; Bei Zhao; Wenjing Zhu; Tiantian Wang; Yu Peng (BMC, 2022)
Abstract Background Scutellaria barbata D.Don (SBD) is derived from the dried whole plant of Labiate which has been widely used to treat patients with multiple cancer. It was previously reported that the ethanol extract of SBD is able to promote apoptosis, and inhibit cell proliferation and angiogenesis in cancer. Materials and methods CCK8, Edu assays and colony formation assay were performed to assess the effect of SBD on PCa cell growth. Effect of SBD on apoptosis and cell cycle was detected by flow cytometry. Transwell and wounding healing assay were conducted to detect the invasion and migration activities of PCa cells. Western blot was employed to detect the protein expression. 2RRV1 mouse xenograft model was established to detect the effect of SBD on prostate cancer. Angiogenesis was analysed by coculturing PCa cell lines and HUVECs. Results The results showed that SBD induced a significant decrease in cell viability and clonogenic growth in a dose-dependent manner. SBD induced cell apoptosis and cell cycle G2/M phase arrest by inactivating PI3K/AKT signalling pathway. Treatment with SBD also significantly decreased the cell migration and invasion via phenotypic inversion of EMT that was characterized by the increased expression of E-cadherin and Vimentin, and decreased expression of N-cadherin, which could be partially attributed to inhibiting PI3K/AKT signalling pathway. Subsequently, using AKT inhibitor MK2206, we concluded that PI3K/AKT are also involved in cell apoptosis and metastasis of PCa cells stimulated by SBD. Apart from its direct effects on PCa cells, SBD also exhibited anti-angiogenic properties. SBD alone or conditioned media from SBD-treated PCa cells reduced HUVEC tube formation on Matrigel without affecting HUVEC viability. Furthermore, 22RV1 xenograft C57BL/6 mice treated with SBD in vivo showed a significant inhibitory in tumour size and tumour weight without toxicity. In addition, administration with medium- or high-dose of SBD significantly inhibited the cell proliferation and enhanced the damage to tumour tissues. Conclusions Collectively, our in vitro and in vivo findings suggest that SBD has the potential to develop into a safe and potent alternative therapy for PCa patients.